WORLD EXPERIENCE IN THE DEVELOPMENT OF THE ENERGY MANAGEMENT SYSTEM AND PROSPECTS FOR ITS IMPLEMENTATION IN UKRAINE - Ажаман, Ірина Анатоліївна; Хабіб, Алі; Пущіна, Наталя В.; Мельничук, Оксана І. (Journal of Strategic Economic Research, 2023)
The study of world experience allows to identify advanced practices, technologies and tools in the field of energy management. Energy efficiency is a key aspect for business and society in general, and the study of global experience in the development of the energy management system allows us to identify: optimal approaches that help reduce energy costs and increase the efficiency of resource use; mechanisms that contribute to the even distribution and use of energy resources, as well as the development of renewable energy sources. At the same time, global practice will contribute to the discovery of effective and advanced technologies that can be implemented to improve energy resource management and achieve sustainable development. Therefore, the research is relevant for understanding the practices of ensuring energy efficiency, sustainability and innovation in this field. The purpose of the article is to study the world experience in the development of the energy management system and to identify proposals regarding the prospects for its implementation in Ukraine. Management of energy resources in order to optimize their use in modern conditions is based on a comprehensive approach that takes into account legal, organizational, economic, geographical, demographic and other aspects. To create an energy saving system at any enterprise, it is necessary to implement energy management, which provides an integrated approach to the optimization of various types of energy. Energy efficiency is an important component of sustainable economic development and ensuring the country's energy and environmental security. The research made it possible to identify a number of measures of economic regulation of energy efficiency, including mandatory norms and state programs. Stimulating measures are also widely used, in particular financial – discounts from energy supply companies, interest-free credit for the introduction of new technologies in the industry, tax breaks or benefits for enterprises that focus on the use of alternative renewable energy sources, state subsidies for the reconstruction of buildings and simplification of the procedure for obtaining permits for the construction of wind and solar power plants or fines for non-compliance with the requirements of federal and local energy conservation authorities. Taking into account the experience, policy in the field of energy conservation in Ukraine should be focused on stimulating flexibility in energy supply, reducing dependence on electricity in heating systems and increasing the share of renewable energy sources in the overall energy balance. It is appropriate to stimulate market participants to environmentally safe and rational use of energy with the help of financial instruments, including through the establishment of energy funds, which can be created with the active participation of banks and large corporations or financed from a tax on electricity distribution tariffs. Funds from such funds can be allocated to enterprises with energy efficiency improvement projects. On the basis of research and taking into account the proposals of the International Energy Agency, the following energy efficiency policy mechanisms are proposed for industrial enterprises of Ukraine: price, regulatory, controlling, informational and motivational.